Transparency, Research And Facebook: The Case Of Facebook.Com/Peace - John, Nicholas (AoIR Selected Papers of Internet Research, 2017)
This paper contributes to critical discussions of access to and working with social media data by casting a skeptical eye over data published daily by Facebook (at facebook.com/peace). These data purport to present the number of friendships formed every day across three violent conflicts. However, close examination of the data raises a number of questions about their validity. This paper lays out some of the reasons to be skeptical about the data, the main one being that the numbers for the Israel/Palestine case, which is examined in detail, appear to be far too high to be credible. For instance, in January 2017 alone, the 1.7m Facebook users in the Palestinian Territories would, on average, all have had to have friended 4.6 Israelis each if, as published, around 7.9m friendships were made during the course of that month. However, conclusive proof that the numbers are invalid would appear to be perpetually out of reach given that Facebook itself will not comment, despite repeated approaches to various position-holders. The current study thus contributes to discussions on the research politics of social media platforms, and especially those that call for greater transparency on the part of Facebook and others. Moreover, with Facebook positioning itself as the key infrastructure for the development of “global community”, it is behoven on internet researchers to demand accountability, especially when Facebook publishes data that support Facebook’s ideology and political agenda.